CRENÇAS DE PROFESSORES DE INGLÊS – LE SOBRE A GRAMÁTICA E O ENSINO DA GRAMÁTICA - Carazzai, Marcia Regina Pawlas; Gil, Gloria (Intercâmbio, 2010)
This article reports on a qualitative study on teachers’ beliefs about grammar and grammar teaching. The study aimed at investigating nine in-service EFL teachers’ beliefs about grammar, the functions the teachers attribute to grammar and grammar teaching in the EFL classroom, and the sources which influence these teachers’ beliefs.